Pengembangan Materi Ismuba (al-Islam) pada Kurikulum 13 Di SD Muhammadiyah 8 KH. Mas Mansur Kota Malang - Nasiruddin Hidayah; Romelah Romelah (Jurnal Ilmiah Iqra', 2022)
Development of Ismuba (al-Islam) Materials on Curriculum 13 at SD Muhammadiyah 8 KH. Mas Mansur, Malang. This study aims to describe the material for Islamic Religious Education and Morals in Curriculum 13 at SD Muhammadiyah 8 KH. Mas Mansur Malang City and its development. This research approach is qualitative, the type of narrative research, data collection by technical observation, interviews and documentation, and using data analysis methods by means of data density, presentation and drawing conclusions. From the results of the study, it was found that the material for Islamic Religious Education and Budi Perkerti at SD Muhammadiyah 8 KH Mas Mansur was the result of the integration of the provisions of the Ministry of Education and Culture of the Republic of Indonesia with the provisions of the Basic and Middle Education Council of the Muhammadiyah Central Executive. And this school has developed material on two aspects, namely on the aspect of fiqh or shari'ah and on the aspect of the Koran which focuses on improving reading and memorization. The recitation of the Qur'an is targeted to be completed during the second semester of the first semester and the target is to memorize a minimum of three juz.